Hubungan Antara Pemanfaatan Laboratorium Sebagai Sumber Belajar Mandiri Dengan Keterampilan Psikomotorik Intranatal Care (APN) Pada Mahasiswa Semester V Akademi Kebidanan Bhakti Asih Cileduk - Al- Bahra; Hj Sumarmi (Akademi Keperawatan RSPAD Gatot Soebroto, 2020)
Based on Midwifery Care II learning, one of the competencies that must be mastered by midwives is conducting Intranatal Care Care. Utilization is intended to increase learning activities, so that the quality and learning outcomes increase. In addition, students who are left behind when teaching theory can catch up because they understand more after the theory is applied during laboratory practice. The general purpose of this study was to determine the relationship between the use of laboratories as a source of independent learning and psychomotor skills in intranatal care in the fifth semester students of the Midwifery Academy Bhakti Asih Cileduk. This research uses descriptive method by using correlation study with cross sectional approach. The population and sample in this study were all semester V students, amounting to 87 people of the Midwifery Academy Bhakti Asih Cileduk. The results showed that 49.43% of students, the level of use of laboratories as a source of independent learning is still relatively low. The level of ability of intranatal care psychomotor skills, seen from the number of students who passed the intranatal care psychomotor skills test, is a high student in utilizing the laboratory, while the number of students who do not graduate is a student who is low in utilizing the laboratory as a source of independent learning. There is a significant relationship between the Utilization of Laboratories as a Source of Independent Learning and Psychomotor Intranatal Care Skills